A bibliometric analysis of acupuncture applied to primary osteoporosis - Yu, Guangbin; Song, Hongyuan; Gao, Yingying; Chen, Guizhen; Xu, Yunxiang (Frontiers in Medicine, 2026)
PurposeRecent research suggests that acupuncture holds significant potential in the treatment of primary osteoporosis. However, a comprehensive bibliometric analysis on this topic has not yet been conducted. Therefore, the aim of this study is to investigate the research hotspots related to acupuncture for primary osteoporosis.MethodsThe Web of Science Core Collection database was searched for relevant publications from 2000 to 2025. Countries, institutions, authors, keywords, and literature were analyzed and visualized using bibliometric software, including CiteSpace 6.4.R1, VOSviewer 1.6.20, BICOMB, gCLUTO, SPSS 27.0, and Microsoft Charticulator, to investigate scientific achievements, research collaboration networks, research hotspots, and research trends.ResultThis study analyzed 775 publications. “Osteoporosis International” is the most-cited journal, and the United States of America conducts the most research output and impact. Guangzhou University of Chinese Medicine is the most prolific institution studying acupuncture for primary osteoporosis; Cortet Bernard and Kanis JA are the authors with the most relevant literature and citations in this field. Keyword analysis revealed that the most frequently occurring term. Additionally, the analysis of the keyword analysis showed that the keyword with the highest number of occurrences was postmenopausal women; The results of the keyword and literature analysis indicate that postmenopausal women, osteoporosis-related complications, Traditional Chinese Medicine, and osteoporosis prevention are emerging as new research hotspots. This bibliometric study provides valuable insights into the research status and trends in acupuncture for primary osteoporosis over the past two decades.ConclusionSupported by high-quality research, acupuncture is increasingly recognized as an effective treatment for primary osteoporosis. Future research should focus on postmenopausal women, osteoporosis-related complications, Traditional Chinese Medicine, and the prevention of osteoporosis.